Changes in blade reaction forces during the curve phase due to fatigue in long distance speed skating - Yuda, J.; Yuki, M.; Aoyanagi, T.; Fujii, N.; Ae, M. (International Journal of Sport & Health Science, 2004)
The kinetic factors to maintain the curve skating velocity of long distance speed skaters were investigated by measuring the changes in blade reaction forces due to fatigue. Eight male long distance speed skaters performed 4000 m skating at maximal effort with an instrumented sensor klapskate. The skaters were videotaped with two synchronized video cameras (60 fields/s) in the mid portion of the curve by using a panning DLT technique. Push-off forces of the left leg and three-dimensional coordinates of the segment endpoints and blades during the left stroke over the 4000 m distance were measured at two points: 650 m and 3450 m. The blade reaction forces (BRF) were defined as the vertical and horizontal components in the coordinate system fixed on the ice, and used to calculate impulse. There were no significant differences in the peak value and impulse of the vertical component of the BRF between the measurements taken at the above two points while those of the horizontal component in the first half were larger than those of the second half. There were significant positive relationships between the peak value and impulse of the horizontal component and the velocity of the center of mass (r=0.721; 0.677, P<0.01). These results indicate that minimizing the decrease in the horizontal impulse of the BRF during the left stroke could be one of important factors to maintain the skating velocity in the curve.